Outpatient vs inpatient Foley catheter induction of labor in multiparas with unripe cervixes: A randomized trial. (30th August 2021) - Hamdan, Mukhri; Shuhaina, Shuib; Hong, Jesrine Gek Shan; Vallikkannu, Narayanan; Zaidi, Syeda Nureena; Tan, Yi Pin; Tan, Peng Chiong
Abstract: Introduction: Multiparous labor inductions are typically successful, and the process can be rapid, starting from a ripened cervix with a predictable response to amniotomy and oxytocin infusion. Outpatient Foley catheter labor induction in multiparas with unripe cervixes is a feasible option as the mechanical process of ripening is usually without significant uterine contractions and well tolerated. Labor contractions can be initiated by amniotomy and titrated oxytocin infusion in the hospital for well‐timed births during working hours as night birth are associated with adverse events. We sought to evaluate outpatient compared with inpatient Foley catheter induction of labor in multiparas for births during working hours and maternal satisfaction. Material and methods: A randomized trial was conducted in the University of Malaya Medical Center. A total of 163 term multiparas (no dropouts) with unripe cervixes (Bishop score ≤5) scheduled for labor induction were randomized to outpatient or inpatient Foley catheter. Primary outcomes were delivery during "working hours" 08:00–18:00 h and maternal satisfaction on allocated care (assessed by 11‐point visual numerical rating score 0–10, with higher score indicating more satisfied). Clinical trial registration: ISRCTN13534944. Results: Comparing outpatient and inpatient arms, delivery during working hours were 54/82 (65.9%) vs. 48/81 (59.3%) (relative risk 1.1, 95% CI 0.9–1.4, p = 0.421) and median maternal satisfaction visual numerical rating score was 9 (interquartile range 9–9) vs. 9 (interquartile range 8–9, p = 0.134), repectively. Duration of hospital stay and membrane rupture to delivery interval were significantly shorter in the outpatient arm: 35.8 ± 20.2 vs. 45.2 ± 16.2 h ( p = 0.001) and 4.1 ± 2.9 vs. 5.3 ± 3.6 h ( p = 0.020), respectively. Other maternal and neonatal secondary outcomes were not significantly different. Conclusions: The trial failed to demonstrate the anticipated increase in births during working hours with outpatient compared with inpatient induction of labor with Foley catheter in parous women with an unripe cervix. Hospital stay and membrane rupture to delivery interval were significantly shortened in the outpatient group. The rate of maternal satisfaction was high in both groups and no significant differences were found.